HAJI FUNDS FOR INFRASTRUCTURE INVESTMENT - Muh Fudhail Rahman; Shubhan Shodiq; Aida Humaira (Al-Qalam, 2020)
As an implementation of the conditions for istita'ah, for person who want to register pilgrimage, the government requires paying amount of money called Biaya Penyelenggaraan Ibadah Haji (BPIH). The accumulated funds have reached untill trillions of rupiah, this accumulation has potential to be developed. Currently, there is debate about the permissibility of using BPIH outside the direct interests of pilgrims such as government infrastructure investment. This research uses normative juridical research. This study also uses a statutory approach and a comparative approach. The results of this study indicate the pilgrimage fund can be invested. However, in terms of the ability to use the pilgrimage funds for investment in government infrastructure, there must be permitted by people who want to go on pilgrimage, or can be used in infrastructure that is directly related to the pilgrimage.